Preparing for a Career in Aquatic Animal Medicine - Ruth Francis-Floyd (EDIS)
If your goal is to be an aquatic animal veterinarian, then obviously the first step is to put together a competitive packet for admission to a college of veterinary medicine. There are also many career opportunities that do not require a veterinary degree. Some suggestions for these career options and how to prepare for them are offered in this document. This document is VM146, one of a series of the Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date January, 2004.